ICASSP 2020 - 2020 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2020
DOI: 10.1109/icassp40776.2020.9053946
|View full text |Cite
|
Sign up to set email alerts
|

The Swax Benchmark: Attacking Biometric Systems with Wax Figures

Abstract: A face spoofing attack occurs when an intruder attempts to impersonate someone who carries a gainful authentication clearance. It is a trending topic due to the increasing demand for biometric authentication on mobile devices, high-security areas, among others. This work introduces a new database named Sense Wax Attack dataset (SWAX), comprised of real human and wax figure images and videos that endorse the problem of face spoofing detection. The dataset consists of more than 1800 face images and 110 videos of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Most 3D PAD datasets are based on wearable hard-resin or silicone masks. Wax figure face databases were reported in [ 34 , 35 ] for super-realistic 3D presentation attack research. For the work presented in this paper, a database has been locally collected as none of the public databases include the type of challenge–response, artefacts and device formats, which are investigated in this paper.…”
Section: State Of the Artmentioning
confidence: 99%
“…Most 3D PAD datasets are based on wearable hard-resin or silicone masks. Wax figure face databases were reported in [ 34 , 35 ] for super-realistic 3D presentation attack research. For the work presented in this paper, a database has been locally collected as none of the public databases include the type of challenge–response, artefacts and device formats, which are investigated in this paper.…”
Section: State Of the Artmentioning
confidence: 99%
“…WFFD [27] introduced the first waxwork dataset, comprising 450 subjects and 2,200 images, significantly increasing fidelity. Similarly, SWAX [60] included images and videos of waxworks. Recent 3D FAS datasets have considered new attack types, ethnic diversity, and complex recording conditions, such as SiW-M [43] with 13 fine-grained attack types, CASIA-SURF CeFA [35] addressing ethnic bias with three ethnicities, and HiFiMask [39] encompassing six lighting conditions, seven recording devices, and six scenarios.…”
Section: Face Anti-spoofing Datasetsmentioning
confidence: 99%
“…A review of current datasets, as shown in Table 1, reveals that most datasets contain either 2D or 3D PAs exclusively. Datasets such as [4, 9-11, 50, 52, 58, 68, 83] feature 2D print or display PAs, while [18,20,28,39,41,57,60,79] include 3D mask or model PAs. Some datasets, such as [31,43,84], encompass both 2D and 3D PAs; however, their diversity remains unsatisfactory due to deficiencies in other elements, such as the absence of high-fidelity 3D models.…”
Section: Introductionmentioning
confidence: 99%